KEDUDUKAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 - Fitri, Sunanda Haizel; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Position the House of Representatives (DPRD), which is referred to as the local legislative body by the public, it is not so. Parliament is one of the elements of the regional administration together with the Regional Head, so that Parliament is a partner of the Regional Head, located parallel to the regional head. Parliament only perform the function of legislation in the area by establishing rules and regulations along the regional level Regional Head, as the regional regulation. The purpose of this study is to determine how exactly the position of Parliament in the regional administration together with the head of the region, as well as how to do with the implementation of the concept of the Unitary Republic of Indonesia (NKRI). This study was included in the normative legal research is the study of law with a review of the legal materials in the form of legislation and study books or library materials available. While the nature of this research is descriptive research is research that provides a clear and detailed picture of the problems studied. The data used is primary data that materials are binding law, as well as secondary data derived from primary legal materials, secondary and tertiary. Data was collected by the method of literature review. The result of this study is that the position of the Council is a partner in running the Regional Head of the regional administration. Indeed, the legislative power is in the realm of the center instead of on the local level, in Parliament ought to be regular penenrapannya position themselves as partners in helping both the Regional Heads in making regulations or the regional administration. Efforts are expected in order to Act No. 23 of 2014 may be revised or amended by the Act which tebaru, so that the absence of any reinterpretation of the Local Government Act.Keywords: Position - Parliament